2022
DOI: 10.1126/science.abn8933
|View full text |Cite
|
Sign up to set email alerts
|

Structure of a Janus kinase cytokine receptor complex reveals the basis for dimeric activation

Abstract: Cytokines signal through cell surface receptor dimers to initiate activation of intracellular Janus Kinases (JAKs). We report the 3.6-Å resolution cryo-EM structure of full-length JAK1 complexed with a cytokine receptor intracellular Box1/Box2 domain, captured as an activated homodimer bearing the Val→Phe (VF) mutation prevalent in myeloproliferative neoplasms. The seven domains of JAK1 form an extended structural unit whose dimerization is mediated by close-packed pseudokinase (PK) domains. The oncogenic VF m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
128
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(136 citation statements)
references
References 76 publications
8
128
0
Order By: Relevance
“…S7), including the Epo-EpoR complex ( 29 ), insulin-insulin receptor complex ( 30 ), and IGF1-IGF1R complex ( 31 ). Moreover, the ~30 Å distance is also comparable to the distance between the two membrane-proximal FERM-SH2 domains of dimeric JAK1 bound to Box1/Box2 motifs of a cytokine receptor on the intracellular side ( 32 ). These consistent observations suggest that bringing the two signaling receptor juxtamembrane domains to ~30 Å apart might be a prerequisite for activating the JAK/STAT pathway.…”
Section: Discussionmentioning
confidence: 99%
“…S7), including the Epo-EpoR complex ( 29 ), insulin-insulin receptor complex ( 30 ), and IGF1-IGF1R complex ( 31 ). Moreover, the ~30 Å distance is also comparable to the distance between the two membrane-proximal FERM-SH2 domains of dimeric JAK1 bound to Box1/Box2 motifs of a cytokine receptor on the intracellular side ( 32 ). These consistent observations suggest that bringing the two signaling receptor juxtamembrane domains to ~30 Å apart might be a prerequisite for activating the JAK/STAT pathway.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, it has been postulated that JAK2 p. R683 mutations disrupt the pseudokinase domain-mediated autoinhibitory interaction, therefore inhibitors that can stabilize this interaction may be able to overcome the effects of these mutations. The recent discovery that apposing JAK1 monomers dimerize via their pseudokinase domains also positions this dimerisation interface as a potentially novel targetable site ( Glassman et al, 2022 ). JAK2 dimerisation may also be mediated via the pseudokinase domains however the full-length structure of JAK2 is yet to be determined.…”
Section: Discussion - Future Outlooksmentioning
confidence: 99%
“…Mutagenesis studies have demonstrated that JAK2 p. V617F confers cytokine-independent signaling activation ( Baxter et al, 2005 ; James et al, 2005 ; Kralovics et al, 2005 ; Senkevitch and Durum, 2017 ). Activating JAK2 mutations, including JAK2 p. V617F, were initially predicted to confer cytokine-independent signaling through disruption of the JH2-mediated autoinhibitory interaction, facilitating mutant-JAK2 dimerization ( Gnanasambandan and Sayeski, 2011 ; Ungureanu et al, 2011 ; Hubbard, 2018 ; Glassman et al, 2022 ). In addition, a recent report using single-molecule microscopy demonstrated that the JAK2 p. V617F mutation confers cytokine-independent dimerization of receptor subunits (50% of the maximum level for TPOR, 25% for EPOR and 10% for hGHR), with a stable time-dependent dimer formation similar to cytokine binding ( Wilmes et al, 2020 ).…”
Section: Jak2 Mutations In Ph-like Allmentioning
confidence: 99%
See 1 more Smart Citation
“…Cytokine receptor chains comprise an extracellular domain that interacts with the cytokine, a single transmembrane domain and a signal-transducing cytoplasmic domain. Upon ligand binding, the cytokine receptor chains on the cell surface associate or are stabilized as dimers or oligomers [ 8 ]. The cytoplasmic domain lacks intrinsic kinase activity and associates with a protein tyrosine kinase of the Janus kinase (JAK) family [ 9 ].…”
Section: Introductionmentioning
confidence: 99%